HPLC-MS/MS measurement of lidocaine in rat skin and plasma. Application to study the release from medicated plaster - Matteo, C; Dovrtelova, G; Di Clemente, A; Frapolli, R; Passoni, A; Ceruti, T; Marsella, G; Cervo, L; Zucchetti, M (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2020)
A simple, sensitive HPLC-MS/MS method was developed and validated for the determination of lidocaine in skin and plasma of rats. The methods were established and validated assessing lower limit of quantitation (LLOQ), linearity, intra and inter-day precision and accuracy, selectivity, recovery and matrix effect. Chromatography was done on a Gemini column embedded with C18 stationary phase (50 mm × 2.0 mm, 5 µm particle size), using a gradient with mobile phases consisting of 0.1% HCOOH in bidistilled water and 0.1% HCOOH in acetonitrile. The mass spectrometer worked with electrospray ionization in positive ion mode and selected reaction monitoring, using target ions m/z 235.10 for lidocaine and m/z 245.10 for lidocaine-d10, used as internal standard. RESULTS: The linearity of the method was in the ranges of lidocaine concentrations 10.0-200.0 ng/mL for skin homogenate (accuracy 94.1-105.5%; R2 ≥ 0.998) and 0.025-2 ng/mL for plasma (accuracy 96.2-104.8%; R2 ≥ 0.996). The intra- and inter-day precision and accuracy determined on three quality control samples (20, 75 and 170 ng/mL for skin and 0.075, 0.4 and 1.5 ng/mL for plasma) were ≤4.2% and 103.8-108.2% for skin and ≤12.4% and 95.5-101.4% for plasma. The LLOQ was 10 ng/mL in skin homogenate and 0.025 ng/mL in plasma. The applicability of the method was demonstrated by measuring lidocaine in skin and plasma after exposure to medicated patches containing 5% lidocaine.
Keywords: stabilita léku; Animals; HPLC-MS/MS analysis; lidokain; Medicated plaster; Linear Models; Tandem Mass Spectrometry; Reproducibility of Results; vysokoúčinná kapalinová chromatografie; transdermální náplast; Pharmacokinetics; kůže; Drug Stability; Lidocaine; lineární modely; reprodukovatelnost výsledků; limita detekce; Chromatography, High Pressure Liquid; Transdermal Patch; Male; tandemová hmotnostní spektrometrie; Skin; krysa rodu Rattus; Limit of Detection; zvířata; mužské pohlaví; Rats